Problems With Using Polygenic Scores to Select Embryos. Issue 10 (October 2021) - Turley, Patrick; Meyer, Michelle N.; Wang, Nancy; Cesarini, David; Hammonds, Evelynn; Martin, Alicia R.; Neale, Benjamin M.; Rehm, Heidi L.; Wilkins-Haug, Louise; Benjamin, Daniel J.; Hyman, Steven; Laibson, David; et al.
Abstract : (Abstracted from N Engl J Med 2021;385:78–86) Embryo selection based on polygenic scores (ESPS) is the principle wherein one can select individualized embryos to transfer as part of in vitro fertilization based on predictions of health and other outcomes derived from genome-wide association studies (GWASs). The majority of human traits including physical characteristics and risk for disease are influenced by cumulative differences in genetic variants.